CONNECTION BETWEEN PARTICLE SIZE DISTRIBUTION AND SETTLING BEHAVIOR BASED ON THE IMHOFF TEST ON OVERBURDEN MATERIALS IN COAL MINES - Inayati
Erosion is one example of environmental problems that occur in mining areas. Erosion has the potential to increase sedimentation in settling pond. Particles carried by erosion generally have varying sizes and are classified as particle size distribution (PSD) which has different depositional properties. Recognizing the sedimentation behavior is necessary to improve the optimal settling pond. In this project, depositional behavior will be monitored using the Imhoff Settling Cone Method. Observations will be carried out for 24 hours and recorded in the first 6 hours. The sediment from the Imhoff test will be screened and analyzed for PSD. Both samples exhibit variations in grain size percentages. One of the samples comprises 20% sand, while the other sample consists of merely 1.6% sand. This pronounced dissimilarity signifies distinctions in depositional characteristics regarding volume height and settling velocity. Additionally, this study will establish a relation between deposition outcomes at Imhoff and Stokes analysis, enabling the derivation of a representative diameter for each settling duration. The depositional behavior is strongly influenced by the particle size distribution (PSD). PSD with a high percentage of sand produces a higher precipitate with a faster time constant (3 hours). Whereas PSD with a higher percentage of silt and clay produces lower deposits with a longer constant time (5 hours). Imhoff's calculations and Stokes' analysis show a 99% correlation. Different PSDs show a relatively similar correlation of Imhoff and Stokes results. So that in determining the speed of deposition of a material can be approached with the Stokes equation.